Liquid Bio-Silica Fertilizer from Ash Solid Waste of Sugar Industry - K. Sumada; L. U. Widodo (Future Science)
The liquid bio-silica fertilizer is one of the fertilizer products in liquid phase containing silica (SiO2), potassium (K) and nitrogen (N). This liquid bio-silica fertilizer is highly needed by some plants that accumulate silica such as rice, sugar cane, corn, palm and others. The presence of silica in fertilizers can improve the quality and quantity of crop yields and keep the silica content in the soil. The liquid bio-silicate fertilizer is produced through three stages of the process, the first process of silica extraction in ash solid waste of sugar industry with a solution of potassium hydroxide (KOH 2N) at 100 C for 2 h will form a potassium silicate solution (K2O.SiO2), the second stage of the process is the ion exchange with the cationic resin to decrease the acidity (pH) to produce liquid potassium silicate fertilizer with various pH (acidity degree), and the third stage is mixing process with the addition of urea solution (nitrogen source). The characteristics of the liquid bio-silica fertilizer were determined based on the concentration of silica (SiO2), potassium (K) and nitrogen (N) as well as the degree of acidity (pH). Based on the results of the research, the bio-silica liquid fertilizer plus has pH from 13,5-11 with 3-5% silica content, potassium (5 - 6,0%) and nitrogen (2-3%).